Legal Protection for Preferred Creditors in Bankruptcy Proceedings Reviewed Based on Justice - Siregar, Surya Lifia; Widianto, Bayu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
As stated in Articles 1134, 1139, and 1149 of the Indonesian Criminal Code and Law No. 37 of 2004 concerning Bankruptcy and PKPU, priority creditors are parties entitled to demand full payment from the heart of the bankrupt based on the nature of their claims. Legal protection for priority creditors in practice often causes problems, even though it appears to be a normative position. This occurred in the case of PT Swissindo Marine, where KPP Pratama Jakarta Tanah Abang I, as a priority creditor with a tax bill of Rp14,134,021,435, did not receive a proper response from the curator. As a result, its application was rejected by the Commercial Court due to procedural issues, and only received a response through a Judicial Review at the Supreme Court. This study aims to analyze the bankruptcy process under Indonesian positive law, determine the types of legal protection for priority creditors, and assess compliance with the principle of justice. The methods used in this study include normative juridical with statutory regulations and descriptive-qualitative analysis using John Rawls's theory of justice. The results of the study indicate that although the protection mechanism for priority creditors has been formally regulated, its implementation has not fully reflected Rawls's Principle of Liberty and Difference Principle. There is a gap between normative protection and practice, weak oversight mechanisms for curators, and the dominance of procedural formalism that contains substantive justice.